How Faculty Create Learning Environments for Diversity and Inclusion - Keonya C. Booker; Gloria D. Campbell-Whatley (InSight, 2018)
The demographics of college campuses are changing and necessitate faculty provide a safe and inclusive environment for learning. The purpose of this study was to examine how faculty establish a sense of belonging in their classrooms, using focus group methodology to explore issues of power, privilege, and access at the postsecondary level. Faculty (N = 33) representing multiple identity groups discussed opportunities and challenges in effectively reaching diverse groups of students. Three thematic categories emerged illustrating how faculty prepare their courses for inclusive content, develop in-class instructional practices including methods regarding assessment, and believe in professional responsibility through persistent role modeling.